2001
DOI: 10.1097/00004872-200104000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Celiprolol stimulates endothelial nitric oxide synthase expression and improves myocardial remodeling in deoxycorticosterone acetate-salt hypertensive rats

Abstract: Myocardial remodeling of DOCA-salt hypertensive rats was significantly ameliorated by subdepressor doses of celiprolol, which may be due to increased eNOS expression in the left ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…However, they increased the protective eNOS mRNA expression in the endothelial system, and therefore increased the release of NO from endothelial cells, which increased the blood supply to damaged areas of the heart. Several studies have reported that eNOS could improve cardiac remodeling [17,18] , which supports our present results. However, ET-1 enhances cardiac remodeling and promotes the development of HF [19] .…”
Section: Differences In Pharmacological Mechanisms Between the Sur2b/supporting
confidence: 93%
“…However, they increased the protective eNOS mRNA expression in the endothelial system, and therefore increased the release of NO from endothelial cells, which increased the blood supply to damaged areas of the heart. Several studies have reported that eNOS could improve cardiac remodeling [17,18] , which supports our present results. However, ET-1 enhances cardiac remodeling and promotes the development of HF [19] .…”
Section: Differences In Pharmacological Mechanisms Between the Sur2b/supporting
confidence: 93%
“…16 Rats received weekly subcutaneous injections of DOCA (30 mg/kg) after right nephrectomy and were given 1% saline as drinking water (DOCA-V, nϭ7). Eight of the 14 remaining DOCA-salt rats were treated with celiprolol (Nippon Shinyaku Co, Ltd) in their drinking water for 5 weeks, and a fresh drug solution was prepared daily (DOCA-Ce, nϭ8).…”
Section: Animal Models and Experimental Designmentioning
confidence: 99%
“…The drug was given at an average dose of 10 mg · kg Ϫ1 · d Ϫ1 (subpressor dose), which was adjusted weekly to the drinking habits of the animals. 16 The remaining 6 DOCA-salt rats were treated with celiprolol plus wortmannin, a PI3K inhibitor (DOCA-CeϩWo, nϭ6). An osmotic minipump (model 2ML4, Alzet Corp) containing wortmannin (1 mg · kg Ϫ 1 · d Ϫ1 ) dissolved in 8% dimethyl sulfoxide was implanted.…”
Section: Animal Models and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations